TikTok como estrategia pedagógica en la enseñanza de ética y valores - José David Cordero Díaz; Gladys Adriana Espinel Rubio; Milton Jesús Vera Contreras (Mundo Fesc)
The study TikTok as a Pedagogical Strategy in the Teaching of Ethics and Values: A Case Study at the Buena Esperanza Technical Institute had the main objective of exploring the impact of the use of the TikTok application as a pedagogical tool in improving the teaching and learning process of ethics and values ​​at the Buena Esperanza Technical Institute. Its theoretical framework was based on the social constructivist approach and the Theory of Technology-Mediated Learning (TAM). The former highlighted the importance of social interaction and collaboration in the construction of knowledge, while the latter examined how technology influences the teaching and learning process, acting as a mediator between the student and the educational content. A mixed-method approach was used, combining elements of quantitative and qualitative research. The study design selected was the case study, allowing an in-depth understanding of the phenomenon in its real context. Techniques such as direct observation, surveys, interviews, and documentary analysis were used for data collection. The target population and sample was the student community of the Buena Esperanza Technical Institute. A sample of 10 active seventh-grade students, approximately 30% of the total population, was selected to ensure the representativeness and validity of the study's findings. Data analysis revealed that the use of TikTok as a pedagogical tool resulted in a significant increase in knowledge retention and understanding of ethical concepts and values, as students showed greater engagement in app-related activities, which translated into improved grades and academic performance. Furthermore, a positive change was observed in students' attitudes toward ethics and values, reflected in greater reflection on their actions and greater empathy toward others. These findings support the feasibility of integrating TikTok into the classroom as an effective strategy to improve the teaching of ethics and values. Likewise, the effectiveness of the TikTok-based pedagogical strategy in improving academic performance and promoting the development of ethical skills and values ​​in students was concluded. The integration of TikTok generated a high level of participation and engagement, as well as a notable increase in interest in the subject of ethics and values. The results suggest a positive impact on various aspects of student learning and behavior, supporting the usefulness of this innovative approach in the educational field.